Doenças associadas ao cavalo-marinho hippocampus reidi (teleostei syngnathidae) em sistema de cultivo experimental, com ênfase em infecções bacterianas - Souto Neto, José Araújo (2016)
This study is a retrospective of five years of experimental cultivation of a seahorse specie Hippocampus reidi. The aim was to characterize and quantify the main diseases of the specie in captivity, associated with water quality parameters in two types of systems (SCF - Closed System Circulation and SI – Isolated unfiltered system), as well an assessment of bacterial infections associated with skin lesions and water during one year. It was recorded 192 ill seahorses in the experimental cultivation over the five years in which individuals with dermatitis were the most frequent, occurring in 46.3% of cases and leading to severe medical conditions as epidermal ulceration, whitish spots along the entire organism and tissue desquamation. Other illnesses as gas bubbles diseases, balance difficulties and sudden death were also observed but to a lesser extent. Samples of ulcerative lesions were collected, using swabs, between april/14 and april/15 of two 2 classes of lesions in the tail and one type in the brood pouch from experimental cultivation seahorses. Samples of water from the water distribution system were also gathered. A total of 119 bacterial strains were isolated. Isolated Bacteria were identified using the 16S sRNA gene according to similarity searches in databases NCBI (National Center for Biotechnology Information) and RDP (Ribosomal Database Project). Among isolated bacterial strains, it was identified 12 species of Bacteria, distributed in seven families. The main families identified in skin lesions of Hippocampus reidi were Micrococcaceae (38.2%), Vibrionaceae (25.5%) and Bacillaceae (23.4%), while the main families founded in water were Pseudoalteromonadaceae (51,4%) and Bacillaceae (34,2%). The number of ill individuals in maintaining systems were directly associated with increased levels of nitrite and ammonia, as well pathogenic bacteria or opportunistic pathogens.